2017
DOI: 10.1128/jcm.02087-16
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of mmpT5 Variants during Bedaquiline Treatment of Mycobacterium intracellulare Lung Disease

Abstract: Bedaquiline (BDQ), a diarylquinoline antibiotic that targets ATP synthase, is effective for the treatment of Mycobacterium tuberculosis infections that no longer respond to conventional drugs. While investigating the off-label use of BDQ as salvage therapy, seven of 13 patients with Mycobacterium intracellulare lung disease had an initial microbiological response and then relapsed. Whole-genome comparison of pretreatment and relapse isolates of M. intracellulare uncovered mutations in a previously uncharacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 37 publications
3
70
0
2
Order By: Relevance
“…Numerous reports have found nucleotide substitutions in selected bedaquiline-resistant mutants, such as A63P and I66M in M. tuberculosis (20)(21)(22). Similar to those findings in M. tuberculosis, a recent study by Alexander et al indicated that one nonsynonymous mutation in the atpE gene was associated with a 50-fold increase in the bedaquiline MIC in M. intracellulare (23). However, no nonsynonymous mutations in the atpE gene that conferred bedaquiline resistance in all six NTM species were identified in our study.…”
Section: Discussionsupporting
confidence: 68%
“…Numerous reports have found nucleotide substitutions in selected bedaquiline-resistant mutants, such as A63P and I66M in M. tuberculosis (20)(21)(22). Similar to those findings in M. tuberculosis, a recent study by Alexander et al indicated that one nonsynonymous mutation in the atpE gene was associated with a 50-fold increase in the bedaquiline MIC in M. intracellulare (23). However, no nonsynonymous mutations in the atpE gene that conferred bedaquiline resistance in all six NTM species were identified in our study.…”
Section: Discussionsupporting
confidence: 68%
“…These nontarget-based mutants primarily harbored single nucleotide polymorphisms (SNPs) in the Rv0687 gene, which is a transcriptional repressor of mmpS5-mmpL5 (18). The involvement of MmpL5 in the resistance to bedaquiline was further evidenced in vitro (19) and supported by recent clinical data (20,21). We were unable to identify and confirm which molecular targets were involved in this efflux pump-mediated tolerance to Q203 in the present study because of the low rate of spontaneous Q203-resistant mutants (ϳ10 Ϫ8 ), with SNPs appearing exclusively in the qcrB gene (A937G leading to T313A) (13).…”
Section: Cells the Number Of Cells Was Determined By Averaging Threementioning
confidence: 64%
“…Mutations in the mmpT5 encoded TetR repressor located ahead of the mmpS5/mmpL5 operon in Mycobacterium intracellulare were associated with modest resistance levels to bedaquiline and clofazimine (Fig. B) (Alexander et al ., ). In addition, high resistance levels to a range of thiacetazone derivatives with potent activity against M. abscessus were found in spontaneous resistant mutants harbouring SNPs or indels in the TetR upstream and divergently orientated to one of three putative mmpS5 ‐ mmpL5 operons (Fig.…”
Section: Introductionmentioning
confidence: 97%